JOB SATISFACTION: ANALYSIS OF SOCIO-DEMOGRAPHIC DATA RELATED TO JOB SATISFACTION AMONG TEACHERS IN THE VIDZEME REGION - Dombrovskis, Aivis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This study analyses the socio-demographic factors of a group of teachers and school headmasters and their job satisfaction. It explores potential correlations and links between socio-demographic factors, the subjects which they teach, their role at the educational institution and the level of job satisfaction. The data were collected from 128 female respondents (N=128) from nine regional communities in the Vidzeme region of Latvia. Respondents were between 22 and 73, with an average age of 49. They were divided into five categories on the basis of age. There were also eight categories for subjects, teaching levels and the performed roles - the arts, the humanities, the social sciences, other sciences, preschool teachers (with students aged 1-7), primary school teachers (7-10), elementary school teachers (7-16) and headmasters. The study shows that job satisfaction among teachers is closely linked to the issue of whether they do or do not have children. Socio-demographic indicators such as partnership, the number of marriages, the number of marriages of their parents, and the existence of siblings - these indicated links, but not statistically significant ones in relation to the job satisfaction of teachers. The Likert scale was used to measure job satisfaction. The collected data were analysed with non-parametric methods.